Critical analysis and innovation propositions to the heat and thermal shock test method of the Brazilian Standard NBR 15575 (2013) - Lorenzi, Luciani Somensi; Stein, Kassio J.; Silva Filho, Luiz Carlos Pinto da (Revista ALCONPAT, 2020)
The tests of Brazilian Standard NBR 15575: 2013 are part of the knowledge of the civil construction industry, but the heat and thermal shock test is innovative and does not have a consolidated history. The research objective is to analyze the testing critically and present proposals based on data meta-analysis. Results showed that the test is very inaccurate in describing the procedure and equipment. This study proposed adjustments and innovations in the test to provide more reliable results, but it does not make propositions regarding visual inspection and the number of cycles. The study concluded that the lack of information on the testing has direct responsibility for the results and that the suggested proposals have the potential to be incorporated.